Aspects regarding the development of tourist potential in Simeria area, Hunedoara county, Romania - Sicoe-Murg, Oana; Mateoc-Sîrb, Nicoleta; Mateoc, Teodor; Peț, Elena; Dumitrescu, Carmen (Acta Carolus Robertus, 2022)
At the beginning of the 18th century, begins to take shape, on the left bank of the Mures River, what today is considered by dedicated specialists "a national monument in the art of parks" and at the same time the oldest and most valuable collection of exotic woody plants and autochthonous from Romania, the wonderful Arboretum from Simeria. The geographical position favors the development of tourism, through the diversity of the landscape (dendrological park, hills, Mureș valley, Strei valley), the natural resources are large, possibility of hiking, the capacity of the territory to support several types of tourism; ecotourism can be developed and promoting the local arboretum brand would include the city of Simeria and the area in the tourist circuits. The aristocratic gardens from Banpotoc (located near Simeria) represent the work (over 15 years) of an italian in love with Romania. Giovanni Savatelli created „I Giardini di Zoe” with love for his granddaughter, Zoe, for our country but also from passion for gardening. In order to promote tourism in Simeria area, we must take into account both the natural and anthropogenic potential, besides it is necessary to preserve the traditions and popular habits of the area and develop these resources.